IN VITRO PHAGOCYTOSIS OF METHICILLIN RESISTANT AND METHICILLIN SENSITIVE STAPHYLOCOCCUS AUREUS BY HUMAN POLYMORPHONUCLEAR LEUCOCYTES - Javed, Numan; Afzal, Nadeem; Tahir, Romeeza; Abbas, Afia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Staphylococcus aureus is a gram positive bacterium that causes a number of diseases such as abscesses, infective endocarditis, septic arthritis, etc. It is acquiring resistance against many antibiotics like methicillin; therefore its control is becoming increasingly difficult. Peripheral blood phagocytes particularly polymorphonuclear leucocytes play an important role in the protective mechanisms against these organisms. Phagocytes interact with bacteria and phagocytose these microorganisms to kill them. Methods: Phenotypically different isolates of Staphylococcus aureus including methicillin resistant Staphylococcus aureus (MRSA) and methicillin sensitive Staphylococcus aureus (MSSA) were collected from various hospitals of Lahore, Pakistan. Fresh polymorphonuclaer leucocytes were obtained from healthy individuals by centrifugation using FicolHypaque gradient combined with dextran sedimentation. Microbiological method was used for the determination of phagocytic index of phenotypic variants of Staphylococcus aureus. Results: A significant difference was observed between the phagocytic index of both bacterial groups. MSSA group showed the Mean±SD of 79.46%±3.9 while MRSA group showed 72.35%±2.5. Conclusion: Significant difference in phagocytic index indicates that it can be one of the mechanisms of MRSA to evade host immune system as compare to MSSA. Keywords: MRSA, MSSA, Phagocytic index, Polymorphonuclear leucocytes